Beyond Binary Opposition: Reconfiguring Islamic Responses to Western Modernity through Resistance, Adaptation, and Post-Secular Synthesis - Musonif, Irfan; Muhamad Ibnu Athoillah; Binti Khuzaemah; Syifa Salsabila; Kholid Mawardi (IHSAN : Jurnal Pendidikan Islam, 2026)
The relationship between Islam and Western modernity has frequently been framed within a binary opposition between acceptance and rejection, limiting a nuanced understanding of its complexity. This study reconceptualizes Islamic responses as a dynamic and processual configuration encompassing resistance, adaptation, and post-secular synthesis. Employing a qualitative interpretive approach, this research utilizes reflexive thematic analysis of contemporary academic literature (2020-2025) to identify latent patterns in the discourse on Islam and modernity. The findings indicate that resistance operates as an epistemological critique of Western modernity, while adaptation reflects selective and strategic engagement with modern institutional and technological structures. More significantly, the study identifies an emergent post-secular synthesis in which Islamic values and modern rationality are integrated, generating hybrid epistemic and socio-cultural formations. Unlike prior studies that examine Islamic responses in fragmented domains, this research integrates ideological, institutional, and epistemological dimensions within a unified analytical framework. In doing so, it bridges modernization theory, multiple modernities, and post-secularism into a coherent conceptual model. The study contributes by shifting the analytical paradigm from binary categorization to a dialectical and process-oriented perspective. These findings provide a theoretical foundation for future empirical research to examine how such configurations manifest across diverse socio-cultural contexts.